Know Your Limits. Issue 4 (4th October 2018) - Forest, Jerry
Abstract : Process safety professionals continue the elusive search for effective leading indicators. The search is for the one indicator to prevent process safety incidents. API RP 754 has already defined Tier 3 leading indicators as challenges to safety systems. Challenges include safe operating limit (SOL) excursions as well as demands on safety systems. If chosen correctly, SOLs can be successful leading indicators for incident prevention. In fact, SOLs can be a leading indicator to other safety system challenges, including pressure relief devices and safety instrumented system activations. The process Celanese used to revamp our SOLs is called Know Your Limits . It involves a rigorous review of SOL set points; complete documentation of the technical basis for selection; documentation in standard operating procedures and operator certification/recertification materials; operator training; incident reporting of challenges; and integration with other process safety elements including alarm rationalization and management. A method to measure program effectiveness is presented. Know Your Limits has contributed to our success in reducing loss of primary containment incidents.1 © 2018 American Institute of Chemical Engineers Process Saf Prog 37: 498–501, 2018